KORELASI UKURAN TUBUH TERHADAP BOBOT BADAN KAMBING SABURAI DI UPTD PEMBIBITAN PETERNAKAN DI KABUPATEN PESAWARAN: Correlation of Body Size To Body Weight of Saburai Goats In Uptd Livestock Breeding, Pesawaran Regency - ahmad khairisman S M; Novi Eka wati; Kunaifi Wicaksana (Wahana Peternakan, 2022)
ABSTRACT The research was conducted with the aim of knowing the correlation between body size and bodyweight of Saburai goats. The study was carried out using secondary data in the form of recordings of 49 saburai goats which were divided into 5 age groups, namely group 1 (birth), group 2 (age 3 months), group 3 (age 6 months), group 4 (age 9 months) and group 5 (12 months old). The results showed that the correlation between chest circumference and body weight for age at birth, 3 months, 6 months, 9 months, 12 months was (0.78; 0.81; 0.81; 0.80; 0.70), then body length to bodyweight for each age group at birth, 3 months, 6 months, 9 months, 12 months, namely (0.55; 0.80-0; 74; 0.68; 0.66) and gumba height to birth weight , 3 months, 6 months, 9 months, 12 months ie (0.62; 0.77; 0.77; 0.73; 0.48) in saburai goats. The conclusion that can be drawn based on the results of the study is that the chest circumference of the Saburai goat has the highest correlation value to body weight, the second highest is body length to body weight and body height has the lowest correlation to body weight. Keywords : Age, Body size, body weight